Host plant adaptation during contemporary range expansion in the monarch butterfly. (9th January 2020) - Freedman, Micah G.; Jason, Christopher; Ramírez, Santiago R.; Strauss, Sharon Y.
Abstract: Herbivores that have recently expanded their host plant ranges provide opportunities to test hypotheses about the evolution of host plant specialization. Here, we take advantage of the contemporary global range expansion of the monarch butterfly ( Danaus plexippus ) and conduct a reciprocal rearing experiment involving monarch populations with divergent host plant assemblages. Specifically, we ask the following questions: (1) Do geographically disparate populations of monarch butterflies show evidence for local adaptation to their host plants? If so, what processes contribute to this pattern? (2) How is dietary breadth related to performance across multiple host species in monarch populations? (3) Does the coefficient of variation in performance vary across sympatric versus allopatric hosts? We find evidence for local adaptation in larval growth rate and survival based on sympatric/allopatric contrasts. Migratory North American monarchs, which have comparatively broad host breadth, have higher mean performance than derived nonmigratory populations across all host plant species. Monarchs reared on their sympatric host plants show lower coefficient of variation in performance than monarchs reared on allopatric hosts. We focus our discussion on possible mechanisms contributing to local adaptation to novel host plants and potential explanations for the reduction in performance that we observed in derived monarch populations.